SOME “EXOTIC” INFORMATION SOURCES THAT HAVE BEEN DISCOVERED DURING THE SELECTION OF SERIAL PUBLICATIONS TO SUPPORT RESEARCH IN ENERGY SECURITY, ENERGY CONSERVATION AND ENERGY EFFICIENCY TECHNOLOGIES AND TECHNIQUES: ADVANTAGEOUS ADDITION FOR “PROFESSIONAL READING” OF A POWER ENGINEERING EXPERT - V. S. Lazarev; I. V. Yurik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
This work is a fragment of ongoing research aimed at creating a comfortable information environment that provides access to the publications of international scientific journals and other periodicals and continuing publications that are necessary to support qualitative performance of research in Priority Directions of the Research and Technical Activities in the Republic of Belarus for 2016–2020. During the citation analysis-based selection of the world scientific serial publications apposite for a qualitative performance of research in energy security, energy conservation and energy efficient technologies and techniques with the use of the data of Journal Citation Reports® (which basic results are available at: https://figshare.com/articles/energy_sec_xlsx/5606053/2) a noticeable amount of non-serial items was also found out in addition to serial publications, as well as some publications that, though being serial, did not look typical to be used in the research activities. Individual consideration of each such “exotic” information source confirmed, however, that their noticeable citedness by the world experts in power engineering looked quite natural. Moreover, it becomes clear that these (apparently wrongly) reflected in Journal Citation Reports® information sources are, however, not an “information noise”, but a useful addition to the “professional reading” of power engineering experts. Since these sources are publicly available via the Internet, it was decided just to recommend them for inclusion in the “professional reading” of the CIS power engineering experts, providing the latter with URLs and brief recommendations for the use. All the mentioned data is given in the present article. As for the species structure of the information sources included in our reference list, there are: a database with online access; web-sites of news agencies; web-site of the International Energy Agency; statistical yearbooks and the electronic resources exposing them, annual reports of governmental and intergovernmental organizations; the online version of the newspaper (“The Guardian”).